Efficacy of Hypertension Self-Management Classes Among Patients at a Federally Qualified Health Center - Eck, Cameron (Prev Chronic Dis, 2021)
Structural racism has contributed to persistent racial disparities in hypertension control, with Black men suffering the highest prevalence of uncontrolled hypertension. Lincoln Community Health Center, our urban Federally Qualified Health Center (FQHC), aimed to use hypertension self-management classes to improve hypertension control among our clinic patients, particularly Black men. Patients attending classes learned about hypertension, were given blood pressure cuffs to use at home, and had the opportunity to speak to physicians in a group setting. We used a nonexperimental quality improvement intervention design to identify baseline differences between participants who attended multiple classes and those who attended only 1 class. Participants who attended multiple classes, most of whom were Black men, achieved an average blood pressure reduction of 19.1/14.8 mm Hg. Although the classes were effective, current policies around health insurance reimbursement and federal quality reporting standards hamper the ability of health care providers to implement such patient education initiatives.